O‘ZBEKISTONDA ZAMONAVIY KO‘NGIL OCHAR SAVDO MAJMUASINING SHAKLLANISH TAMOYILLARI - Abdinazarov Kozim Zaripovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: construction of any buildings and artificial structures, residential, public, industrial and agricultural buildings. it is the basis of bridges, bulk buildings, pipelines and structures. The main part of the costs for the construction of buildings and structures falls on structures.This article discusses the principles of the formation of a modern shopping and entertainment complex in Uzbekistan.